Scrolling to Salvation: Memahami Karya Keselamatan Melalui Media Tiktok - Imanuel Teguh Harisantoso; Izak Yohan Matriks Lattu; Cleta V. K Maitimu; Dylan Azarya Radja Hedo; Kenneth Garland Numa Jermy; Melfa F. Sufmera; Binsar Ariel Natanael Tambun; Anggi Toabnani; Claudy Yohana Debora Emor; Simri R. Runesi; Roland Van Ratu Elo (Universitas Kristen Satya Wacana Salatiga, 2025)
TikTok can serve as an ecclesiological space, a platform for exploring the meaning of life, nurturing faith, and fostering spiritual growth. From a missiological perspective, TikTok offers opportunities for proclaiming salvation and facilitating digital encounters that engage individuals in meaningful ways. The primary aim of this PkM initiative is to educate and mentor the youth of GMIT Betania Teubaun Rabe, Kupang, East Nusa Tenggara. The project seeks to develop their capacity to utilize TikTok as a tool for church service and the proclamation of the Gospel of Christ. The approach integrates lectures, collaborative discussions, and hands-on training in using TikTok as a medium for ministry and digital evangelism. As a tangible outcome, the youth, alongside the church's multimedia team, were encouraged to form a church creative team. This team is tasked with producing innovative social media content for the church. Participants received training on creating engaging and meaningful videos, utilizing accessible and cost-effective tools such as standard smartphones.